Emergence and early survival of early versus late seral species in Great Basin restoration in two different soil types. Issue 4 (8th June 2015) - Uselman, Shauna M.; Snyder, Keirith A.; Leger, Elizabeth A.; Duke, Sara E.; Marrs, Rob
Abstract Questions How does performance of a native early seral seed mix during early life stages compare to that of a late seral mix when seeded with Bromus tectorum or Taeniatherum caput‐medusae? Does either mix reduce survival of exotic annual grasses during early life stages, and does this effect differ with soil type? Is exotic performance stronger in one soil type, and does native performance when growing with exotics differ between soil types as a result of exotic preference? Location University of Nevada Agricultural Research Station, Reno, NV, US. Methods We compared seedling emergence and early survival (Nov through May) of two native seed mixes, each composed of grass, forb and shrub functional groups, when growing with B. tectorum or T. caput‐medusae in soils of contrasting texture (sandy loam and clay loam). Natives were also seeded without exotics. Performance of an early seral mix was compared with that of a late seral mix representative of species commonly used in Great Basin restoration. Results Comparing emergence and survival probabilities, early seral natives generally outperformed late seral natives when growing with exotics and had earlier emergence timing, although results differed among functional groups and soil types. In contrast, survival probabilities did not differ between the early and late seral mixes when growing without exotics. Within each seed mix, native grasses exhibited the highest emergence probabilities of the functional groups. Natives did not suppress exotics in early life stages. Performance of B. tectorum was higher on sandy loam, while T. caput‐medusae was highly successful in both soil types. Performance of native functional groups differed by soil type when growing with exotics but did not differ when growing without exotics. Survival of native grasses, in particular, was generally higher on sandy loam when growing with exotics. Conclusions Findings suggest that the use of early seral natives in areas invaded by exotic annual grasses may improve early seedling survival in the Great Basin, in comparison to the use of later seral species in traditional seed mixes. Variation in native performance in the two soil types may be helpful in tailoring seed mixes to different sites.